(untitled) (Italiano LinguaDue, 2021)
Il presente contributo descrive i principi e gli obiettivi di materiali fraseodidattici rivolti ad apprendenti dell’italiano come L2, elaborati nell’ambito del progetto “LeKo – Combinazioni lessicali e linguaggio tipizzato in contesto plurilingue”, in collaborazione tra l’Università di Innsbruck ed Eurac Research. Frutto di un approccio multidisciplinare, il progetto integra concetti teorici, metodi e risorse della ricerca fraseologica, della didattica basata sui task e della linguistica dei corpora (in particolare dei learner corpora). Attraverso la presentazione di un’unità didattica e della cornice narrativa che fa da sfondo al libro di testo, vengono messe in luce le caratteristiche salienti di un modello fraseodidattico orientato all’azione, nel rispetto di principi fondamentali della glottodidattica moderna, quali ad esempio l’autenticità del materiale e la possibilità di sviluppare le competenze comunicative in diverse situazioni della vita quotidiana e il ricorso a contesti multimediali. Developing lexical and phraseological competence through tasks. A contribution to the development of teaching material for Italian L2 The present article describes the principles and objectives of phraseodidactic materials for L2 learners of Italian. The materials were produced as part of the research project “LeKo – Lexeme combinations and typified speech in a multilingual context”, a collaboration between the University of Innsbruck and Eurac Research. Resulting from a multidisciplinary approach, the project includes theoretical concepts, methods and resources from phraseological research, task- based language teaching, as well as corpus linguistics (especially of learner corpora). By presenting a teaching unit and the textbook’s narrative framework, we will illustrate the main characteristics of the action-oriented phraseodidactic model that also reflects fundamental principles of modern language teaching such as using authentic materials, allowing students to develop their communicative skills in different everyday situations and employing various forms of media.